Regional crime trends, local authority and community safety partnership crime trends data for Scotland, England and Wales: violence and burglary - Bates, Ellie (UK Data Service, 2017)
This dataset provides police recorded crime counts and related resident population estimates for all violence and burglary (housebreaking in Scotland) (data on burglary and violence is provided separately) for the financial years 2004-5 to 2015-16. This is a longitudinal data set with data aggregated by year to financial years (1st April in one year to 31st March in following year) for the years 2004-5 to 2015-16 inclusive. Data runs from 1st April 2004 as this is the date from which all nations had national crime recording standards for police recorded crime. The dataset has been prepared to provide comparative data at the regional level - in this case - local authority districts for Scotland, and Community Safety Partnerships (CSPs) as at 2015-16 in England and Wales. Data for England and Wales are directly comparable. As Scotland, and England and Wales, have different legal systems, and different police crime recording standards, the recorded crime definitions of violence and burglary (housebreaking) used here aim to provide the best available comparable data between the countries, but precise definitions of violence and burglary (housebreaking) used in the Scottish, and the English and Welsh, legal systems are not the same. Community Safety Partnerships (CSPs), previously also called Crime and Disorder Reduction Partnerships, are comprised of one or more English or Welsh district or unitary local authorities. Over time, some CSPs have merged and / or added additional local authorities to the partnership, this may also lead to change of partnership name. The CSPs used here are those current as listed in Home Office open data tables on recorded crime for 2015-16 (downloaded in February 2017). Police recorded crime data are data reported to and recorded by the police. Not all crimes are reported to the police, and not all reported crime are subsequently recorded. Data used from England Wales to derive this dataset do not have National Statistics status, this was withdrawn in January 2014. Data for Scotland had National Statistics status withdrawn in July 2014 but reinstated in September 2016. These data are derived entirely from open data as defined in the Open Government Licence version 3 (OGL3). The Applied Quantitative Methods Network (AQMeN) Phase II is a Research Centre that aims to develop a dynamic and pioneering set of projects to improve our understanding of current social issues in the UK and provide policy makers and practitioners with the evidence to build a better future. Three principal cross-cutting research strands will exploit existing high-quality data resources: Education and Social Stratification will focus on social class differences in entry to, progression in and attainment at tertiary education and how they affect individuals' labour market outcomes and their civic participation; Crime and Victimisation will explore the dramatic change in crime rates in Scotland and other jurisdictions and examines the determinants and impact of criminal careers amongst populations of offenders; and Urban Segmentation and Inequality which will create innovative new measures of social segmentation and combine these with cutting-edge longitudinal and sorting-model techniques to explore the causes of neighbourhood segmentation, household location choice and neighbourhood inequalities. Five additional projects will focus on the referendum on Scottish independence, location dynamics and ethnicity and exploiting existing datasets. The research will fed into training activities and knowledge exchange events aimed at boosting capacity in quantitative methods amongst the UK social science community.